Oocyte structure and ultrastructure in the Mexican silverside fish Chirostoma humboldtianum (Atheriniforme: Atherinopsidae) - Cárdenas, R. (2008)
The structural and ultrastructural features of gonads from endemic Mexican fish have received scarce attention. This study describes the histological and ultrastructural characteristics of oocyte from Chirostoma humboldtianum. The ovary is asynchronic, and as such, most phases of oocyte development are found in the same ovary. The complete process of oogenesis was divided in five stages: oogonium and folliculogenesis, primary growth, cortical alveoli and lipid inclusions, vitellogenesis, and maturation. The presence of big filaments, which appear at the end of primary growth, induces some common follicular adaptation. During primary growth, abundant ribosomes, the rough endoplasmic reticulum, and mitochondria are grouped in the cytoplasm. At the end of this stage, the Z1 layer of the chorion is developed, while microvilli start to be evident. In the cortical alveoli and lipid droplets phase, intense PAS positive vesicles, some of them containing nucleoid material, are observed in the peripheral cytoplasm and the lipid droplets take a more central position. In vitellogenesis, the proteic yolk accumulates in a centripetal way while the chorion is completely formed. During maturation, the germinal vesicle migrates to the animal pole, meiosis is restored, and there is nuclear breakdown. The oocyte increases its size and holds some oil droplets and a big fluid mass of yolk. On the outside, filaments completely surround the oocyte.